Herpetofauna distribution in different land cover types of West Java, Indonesia - ERRI NOVIAR MEGANTARA; JIRJIZ JAUHAN; SYA SYA SHANIDA; TEGUH HUSODO; DERRI ACHMAD FAUZI; RANDI HENDRAWAN; INDRI WULANDARI; YUANSAH YUANSAH (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Megantara EN, Jauhan J, Shanida SS, Husodo T, Fauzi DA, Hendrawan R, Wulandari I, Yuansah. 2022. Herpetofauna distribution in different land cover types of West Java, Indonesia. Biodiversitas 23: 2990-2999. Herpetofauna is very sensitive and can be used as a biodiversity indicator. Herpetofauna can experience environmental stress due to agricultural activities, tourism, and other disturbances that result in habitat loss. Herpetofauna can be found on various land covers, such as natural forests and human-modified land. This study revealed species associated with natural forests, human-modified land, and both. This study aims to investigate: 1) herpetofauna distribution based on land cover types and 2) the disturbance that threatens the herpetofauna habitat in West Java. Visual Encounter Survey combination with the Auditory Encounter Survey, was applied in this study. The result of this study, the species were found in the natural forest (53 species), human-modified land (63 species), and crater (2 species). Thirty-nine species were found both in the natural forest and human-modified land. The habitat disturbance potentially threatens the species, such as land clearing (it will affect the microclimate of land cover), roadkill, infrastructure development, and tourism activities.